Medical management of coral reef aorta through optimised diuretic use and angiotensin receptor blockade. Issue 6 (2nd June 2021) - Oey, Nicodemus Edrick; Tulsidas, Haresh; Nadarajan, Krithikaa
Abstract : Coral reef aorta (CRA) is a rare condition with potentially devastating complications. It is characterised by atherosclerotic calcification and stenosis of the visceral part of the aorta, usually occurring at the juxtarenal or suprarenal locations, and causing refractory hypertension and renal dysfunction. Surgical intervention, which is the recommended definitive treatment, is associated with significant morbidity and mortality. Endovascular stenting has been reported to be an alternative management option. To the best of our knowledge, this is the first case report to describe medical management of a patient with CRA with diuretics and angiotensin receptor blockade without surgical treatment.